Challenges in researching violent deportation practices and working with street-level bureaucrats - Borrelli, Lisa Marie (Research methods in deportation, 2024)
Studies on so-called irregular migration have discussed power inequalities and asymmetries that can be disclosed when analysing asylum encounters, decision-making practices of bureaucrats within the migration and border regime and deportation practices. As researchers within such a field, we find ourselves immersed in structural violence, bureaucratic actions and individual stories that shape migration regimes. The chapter discusses ethical challenges of researcher positionality and transparency when it comes to research in public administration tasked with the deportation of non-citizens. Instead of ruling such research out, I elaborate on the question ‘on whose side are we on?’ and how we could deal with situations where not all individuals that we encounter are informed about our role. Based on ethnographic material, which includes observations and interviews within the Swedish and Swiss deportation regimes, I connect these issues to questions of knowledge production to support critical perspectives on organisational ethnography.